Enhancing eork effectiveness and stability through AML/CFT compliance and training regime in bKash Limited - Tabassum, Nujhat (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.